Investigation of structural, electronic and thermoelectric properties of XCUOTE (X: BI, CE, LE) with GGA-WC exchange correlation functional - Mohd Amin, M. A. I. (Penerbit UTM Press, 2016)
Linearized augmented plane wave plus local orbitals (LAPW + lo) method designed within density functional theory (DFT) has been used in this study to calculate the structural, electronic and thermoelectric properties of XCuOTe (X=Bi, Ce, La). Generalized gradient approximation, Wu-Cohen (GGA-WC) parameterized exchange correlation functional, was used. The structural and electronic calculations have a good agreement with previous study. For thermoelectric calculation, semi empirical Boltzmann approach implemented in BoltzTraP package was used to calculate Seebeck coefficient, electronic conductivity as well as thermal conductivity. By referring to previous studies, the results have good agreement with them. In addition, the Seebeck coefficient of these materials was calculated as a function of the chemical potential at temperatures 300K, 600K, and 900K. Our calculations highlight suitability of these materials for applications in thermoelectric devices.